Growth Ability of Lactobacillus plantarum Bacteria on the Chicken Egg White at Different Fermentation Time - . Nahariah; A. M. Legowo; E. Abustam; A. Hintono; Y. B. Pramono; F. N. Yuliati (Fakultas Peternakan, Universitas Hasanuddin, Makassar, 2013)
Bacterial decomposition on meat, dairy and fish protein have been carried out extensively but has not been done on egg white. In order to break the proteins down, the bacteria need to grow well on the medium. This study aims to become preliminary information to determine the growth ability of L. plantarum bacteria in the egg whites with indicators: total bacteria, pH, and, total acids formed by different fermentation treatments. The study was conducted according to completely randomized design using different time of fermentation as treatments (18: 24: 30 hours) on 150 eggs from the same chicken farm, bacteria L. plantarum 0027 FNCC isolated from milk. Replication for each treatment was five. The results showed that fermentation time significantly increased the total bacteria, total acid and decreased pH during the fermentation process. The difference between total bacteria increase was significant between the 18-hour fermentation time and both the 24 and the 30 h fermentation time, namely 5.884 ± 0.157 log CFU/g, 6.035 ± 0.024 log CFU/g, and 6.131 ± 0.095 log CFU/g respectively, although the difference between the 24 and 30 h fermentation time was insignificant. The difference of total acid production was significant between the 18 and the 24 and the 30-hour fermentation time, i.e. 0.077±0.014%, 0.014%±0.167 and 0.171 ±0.017% respectively, altohough once again the difference between the 24 and 30 hour fermentation time. pH decrease during the fermentation time process showed a significant difference between the 18-hour fermentation time and the others, namely 7.689±0.035, 6.434±0.501 respectively 6.353±0.65, and again the difference between the 24- and the 30-hour fermentation time was not significant. The 24-hour fermentation time may incrase growth ability ofbacteria L. plantarum on egg white.